The Impact of Trade War between the United States of America And the People’s Republic of China towards the Economic Conditions of ASEAN Countries during 2018-2019 - Samuel Frenly Reinhard Kusila Kusila; Raharyo Anggara (Universitas Muhammadiyah Malang, 2022)
The trade war between the United States and the People's Republic of China has had a significant global economic impact. This war started from a sense of threat from the US under the administration of President Donald Trump against the rise of China which will replace the US position as a position in leading the world. Therefore, President Trump has imposed tariffs on China to suppress the country's economy. However, China did not remain silent and took the same action against the US so that a trade war ensued. This raises the question of how the trade war can occur and how the trade war can have a positive impact on other countries, one of which is ASEAN which is experiencing an economic increase caused by rising foreign investment and the movement of companies from China to avoid tariffs that are high. Worn by Chinese exports to the US. Therefore, this article will analyze how the US took a unilateral decision to impose sanctions on China and how the trade war could be profitable and how the US and China could easily cooperate with ASEAN in the midst of a trade war.Keywords: Trade war, ASEAN, Economic Growth, Trade Partnership, Investment, USA, China, Cooperation.